Legal Protection against the Guarantee of the Normative Rights of Workers after the Issuance of Law Number 11 Year 2020 Concerning Copyright - Surya Perdana (Randwick International of Social Science Journal, 2022)
One problem that gets the most attention is the issue of fulfilling workers' rights. The emergence of disputes between workers and employers or employers is due to the existence of rights between workers and employers that are not carried out by each party. Although there has been Law (UU) No. 13 of 2003 concerning Manpower, this law has not been able to mediate when there are workers' rights that are not fulfilled by employers. The issuance of Law Number 11 of 2020 concerning Job Creation makes the fate of workers worse, because this law is more oriented towards increasing economic investment and facilitating business permits, but on the other hand, it ignores the normative rights of workers